2023
DOI: 10.3390/life13071500
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Rhamnosyl Residue of Ouabain in the Activation of the Na,K-ATPase Signaling Function

Abstract: The signaling or non-pumping Na,K-ATPase function was first observed by us in the nociceptive neuron; Na,K-ATPase transduced the signals from the opioid-like receptors to NaV1.8 channels. This study elucidates the role of the rhamnosyl residue of ouabain in the activation of the Na,K-ATPase signaling function. The effects resulting from activation of Na,K-ATPase signaling by the Ca2+ chelate complex of ouabain (EO) are not manifested upon removal of the rhamnosyl residue, as demonstrated in viable cells by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(100 reference statements)
0
2
0
Order By: Relevance
“… 357 , this appears to be the first claim that the sugar moiety in ouabain has a specific role in signaling. The same authors also suggest, based upon modeling studies of the polyhydroxylated steroid cores in ouabain and ouabagenin, that both steroids might chelate Ca 2+ ions and that the resultant NKA bound complexes lead to calcium-related ionic interactions with Glu-116 and Glu-117 ( 366 ). We suspect, however, that Ca 2+ chelates in the circulation are likely to be relatively unstable.…”
Section: Cts Binding By the Nka Is A Complicated Affairmentioning
confidence: 98%
See 1 more Smart Citation
“… 357 , this appears to be the first claim that the sugar moiety in ouabain has a specific role in signaling. The same authors also suggest, based upon modeling studies of the polyhydroxylated steroid cores in ouabain and ouabagenin, that both steroids might chelate Ca 2+ ions and that the resultant NKA bound complexes lead to calcium-related ionic interactions with Glu-116 and Glu-117 ( 366 ). We suspect, however, that Ca 2+ chelates in the circulation are likely to be relatively unstable.…”
Section: Cts Binding By the Nka Is A Complicated Affairmentioning
confidence: 98%
“…On a related topic, in primary sensory neurons, the ouabain-NKA-Src complex apparently is involved in transducing signals from opioid-like receptors to NaV1.8 channels ( 364 ). In this system, ouabain has an antinociceptive effect ( 365 ) and it has been suggested that the rhamnosyl residue of ouabain is critical because ouabagenin did not activate signaling ( 366 ). Although it has long been recognized that the rhamnose moiety contributes to the high-affinity binding of ouabain to NKA, e.g., Ref.…”
Section: Cts Binding By the Nka Is A Complicated Affairmentioning
confidence: 99%